2004
DOI: 10.1016/j.mad.2004.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Myofibrillar myosin ATPase activity in hindlimb muscles from young and aged rats

Abstract: We tested the hypothesis that Ca 2+ -activated myosin ATPase activity is lower in muscles of aged rats relative to muscles of young rats, independent of changes in myosin isoform expression. Myofibrils were prepared from permeabilized fibers of soleus, plantaris, and semimembranosus muscles of young (8-12 months) and aged (32-38 months) F344 × BN rats and assayed for resting myosin ATPase, Ca 2+ -activated myosin ATPase, and myosin heavy chain (MHC) and myosin light chain (MLC) isoform compositions. Resting my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 38 publications
(58 reference statements)
3
28
0
Order By: Relevance
“…The clearest difference was in Ca 2ϩ regulation: the decrease in Ca 2ϩ regulation of force and myofibrillar ATPase was much more pronounced in peroxidetreated (Figs. 3 and 5) than aged (42,44) muscle. EPR studies revealed the structural basis of this difference: the fraction of myosin heads in the strongly bound structural state in relaxed muscle significantly increased after H 2 O 2 treatment (Fig.…”
Section: Comparison Of Changes In Muscle Function Associated With In mentioning
confidence: 81%
“…The clearest difference was in Ca 2ϩ regulation: the decrease in Ca 2ϩ regulation of force and myofibrillar ATPase was much more pronounced in peroxidetreated (Figs. 3 and 5) than aged (42,44) muscle. EPR studies revealed the structural basis of this difference: the fraction of myosin heads in the strongly bound structural state in relaxed muscle significantly increased after H 2 O 2 treatment (Fig.…”
Section: Comparison Of Changes In Muscle Function Associated With In mentioning
confidence: 81%
“…This result indicates a decrease in the energetic efficiency, a partial uncoupling between ATPase activity and force generation, during contraction in aged muscle. In contrast, under unloaded shortening conditions (isotonic) in the same muscle, aging results in a decrease (16%) in the myofibrillar ATPase activity and a similar decrease in the shortening velocity (Lowe et al, 2004a). These findings (ATPase activity under isometric and isotonic conditions) suggest that the age-related inhibition of contractility may in part be due to changing actin-myosin interactions.…”
Section: Age and Myosin Atpase Activitymentioning
confidence: 84%
“…Skinned muscle fibers from old rodents show a reduction in specific muscle force, indicating a probable impairment in the muscle contractile machinery [41]. It has been shown that old muscle fibers show only a slight decrease in the actin-myosin filament ratio [42], however, the activity of myosin ATPase is substantially reduced [43]. Myosin but not actin oxidative modification levels are also increased in old muscles [22].…”
Section: Discussionmentioning
confidence: 99%